Effect of Incorporating Hematite Powder on Torsional Behavior of High Strength Steel Fiber Reinforced Concrete Members - Abdulhasan, Mohammed S.; Chkheiwer, Aqeel H. (Civil Engineering Journal, 2025)
This research aims to investigate the effect of hematite powder on the first cracking and ultimate torsional resistance, crack patterns, and angle of twist of high-strength concrete beams strengthened with steel fibers under pure torsion. The study was carried out in two stages. The first stage consisted of six hollow cross-section beams to determine the best ratio and type of steel fiber that provide the highest torsional resistance. The second stage aimed to find the optimal ratio of hematite powder that can improve the torsional resistance of high-strength steel fiber-reinforced concrete without causing implementation problems. This was achieved by testing six hollow cross-section beams with hematite ratios of 0.5%, 1%, 1.5%, 2.5%, 3.5%, and 5% as cement replacements. The results showed that using hematite powder up to 2.5% as a cement replacement, combined with a 1.5% mix of steel fibers (50% end-hooked and 50% corrugated), increased both the first cracking and ultimate torque, along with a relative increase in the angle of twist. Additionally, it delayed crack development, reduced crack width, and increased the number of cracks at failure.